An analysis of the implementation of infant nutritional feeding policy : the case of the Limpopo Province - Mudau, S. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
Nutritional deficiencies account for millions of deaths among children under five years of age globally and are common in poorer regions of the world, such as sub-Saharan Africa. Poorer areas such as the Limpopo province, for example, are the most vulnerable and affected. The consensus from the international and local health governance is that there should be continuous nutritional feeding assessments and interventions, especially for children under five years of age in public health facilities. This study analyses the implementation of the Infant and Young Child Feeding Policy in the Limpopo Province, South Africa. The study also specifically explores the implications of the health workers' response to the policy for the optimisation of the health of children under five years of age in the province. The study adopted a desktop descriptive approach. It focused on nutritional feeding assessments, interventions, and administrative practices at all levels of care in Limpopo province, South Africa, from 2014-2019. The study analysed performance indicators of Vitamin A at 12-59 months' coverage, children under five years' acute malnutrition case fatality rate, and the number of facilities accredited for baby-friendly initiatives. The results revealed flaws and omissions in the implementation of this policy in the health facilities. Close monitoring and decisive actions for the improvement of nutritional assessment, community, and individual nutritional education is recommended to improve the health indicators in the province. There is a need for data ownership to ensure full policy implementation from top management to the operational level to improve the reported poor-performing indicators.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Breastfeeding; Feeding policy; Infant; Malnutrition; Nutritional assessment; Vitamin A; Nutrition -- Evaluation; Nutrition -- South Africa -- Limpopo; Malnutrition in infants -- South Africa -- Limpopo; Breastfeeding; Infants -- Care -- South Africa -- Limpopo